PENDAMPINGAN EVALUASI PROSES PENILAIAN KINERJA MELALUI REGULER VISIT DI PT. TATUR UTAMA SEJATI - Teguh Kunarko; Ayundha Evanthi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
PT. Tatur Utama Sejati is an outsourcing company that supplies courier workers to J&T Express as one of its main partners. However, until now, PT. Tatur Utama Sejati has not conducted periodic and independent performance evaluations of the workers it places. The company still relies entirely on performance assessments provided by J&T Express supervisors or coordinators, without conducting direct visits to partner locations (Drop Points). This condition creates a monitoring gap that can affect the quality of worker performance and the continuity of the working relationship with clients. This community service activity aims to introduce and implement a regular visit system as a structured mechanism for periodic performance evaluation, carried out every three to six months by PT. Tatur Utama Sejati independently. The implementation method includes observation, direct interviews, and structured assessment using a performance evaluation form. The results of the activity show that the regular visit program enables PT. Tatur Utama Sejati to obtain direct and objective performance data, identify problems in the field earlier, and improve coordination with J&T Express. This initiative is expected to strengthen the company’s role as a professional outsourcing company that actively monitors the quality of its workers.